Solar chemical composition in the hot gas of cool-core ellipticals, groups, and clusters of galaxies. (23rd July 2018) - Mernier, F; Werner, N; de Plaa, J; Kaastra, J S; Raassen, A J J; Gu, L; Mao, J; Urdampilleta, I; Simionescu, A
Abstract: The hot intracluster medium (ICM) pervading galaxy clusters and groups is rich in metals, which were synthesized by billions of supernovae and have accumulated in cluster gravitational wells for several gigayears. Since the products of both Type Ia and core-collapse supernovae – expected to explode over different time-scales – are found in the ICM, constraining accurately the chemical composition of these hot atmospheres can provide invaluable information on the history of the enrichment of large-scale structures. Recently, Hitomi observations reported solar abundance ratios in the core of the Perseus cluster, in tension with previous XMM–Newton measurements obtained for 44 cool-core clusters, groups, and massive ellipticals (the CHEERS sample). In this work, we revisit the CHEERS results by using an updated version of the spectral code used to fit the data (spexact v3), the same that was used to obtain the Hitomi measurements. Despite limitations in the spectral resolution, the average Cr/Fe and Ni/Fe ratios are now found to be remarkably consistent with unity and in excellent agreement with the Hitomi results. Our updated measurements suggest that the solar composition of the ICM of Perseus is a common feature in nearby cool-core systems.